2007
DOI: 10.1038/sj.leu.2404902
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analyses of the growth inhibitory effects of NCH-51, a novel histone deacetylase inhibitor, on lymphoid malignant cells

Abstract: Recent reports showing successful inhibition of cancer and leukemia cell growth using histone deacetylase inhibitor (HDACi) compounds have highlighted the potential use of HDACi as anti-cancer agents. However, high incidence of toxicity and low stability in vivo were observed with hydroxamic acid-based HDACi such as suberoylanilide hydroxamic acid (SAHA), thus limiting its clinical applicability. In this study, we found that a novel non-hydroxamate HDACi NCH-51 could inhibit the cell growth of a variety of lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
1
37
1
Order By: Relevance
“…We and others have reported that chemical and genetic inhibition of HDACs leads to decreased expression of FLIP mRNA (36)(37)(38)(39)(40)(41)(42)(43). However, the mechanism by which inhibiting HDACs decreases FLIP expression is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported that chemical and genetic inhibition of HDACs leads to decreased expression of FLIP mRNA (36)(37)(38)(39)(40)(41)(42)(43). However, the mechanism by which inhibiting HDACs decreases FLIP expression is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A histone deacetylase (HDAC) inhibitor, vorinostat, was used as described previously. 23 Proteasome inhibitors MG-132 and bortezomib and a heat-shock protein 90 (HSP90) inhibitor alvespimycin were purchased and used in this study.…”
Section: Cmapmentioning
confidence: 99%
“…A number of studies have reported that HDAC inhibition by several HDACIs such as SAHA, MS-275, and NCH-51 leads to accumulation of ROS [72][73][74][75][76]. Furthermore, the resulting …”
Section: Hdaci-induced Oxidative Stressmentioning
confidence: 99%